Strategies for the Preservation of Rare Book Collections at the State Museum of North Sumatra Province - Shabrina, Hulwa Azra; Yusniah, Yusniah (Inkunabula: Journal of Library Science and Islamic Information, 2025)
This study explores the preservation strategies employed for the rare book collection at the North Sumatra State Museum, which constitutes a vital part of the nation's cultural heritage. These rare books possess significant historical and intellectual value, reflecting the trajectory of civilization and the formation of national identity. As a cultural institution, the museum bears a major responsibility to safeguard these collections from deterioration and loss. The primary aim of this research is to identify the preservation strategies implemented by the museum and to examine the challenges encountered during the process. A qualitative method with a descriptive approach was used. Data were collected through direct observation, interviews with museum staff, and documentation analysis of preservation activities. The interview involved a single informant, Herina Eliasta Ginting, who serves as the Rare Book Collection Officer. She was selected due to her direct involvement and extensive knowledge of the conservation processes conducted at the museum. Data were analyzed using the interactive model proposed by Miles and Huberman. The findings reveal that the museum has implemented several preservation measures, including regulation of temperature and humidity in storage areas, physical security measures, and preventive maintenance to avoid potential damage. However, the implementation of these strategies continues to face significant challenges, particularly the limited availability of conservation experts and operational funding. Consequently, enhancing human resource capacity and adopting digital preservation technologies are essential to ensure more effective and sustainable conservation of the collection.AbstrakPenelitian ini membahas strategi pelestarian koleksi buku langka di Museum Negeri Provinsi Sumatera Utara, yang merupakan bagian penting dari warisan budaya bangsa. Buku-buku langka ini memiliki nilai sejarah dan intelektual tinggi yang mencerminkan perjalanan peradaban serta identitas nasional. Museum sebagai institusi budaya memiliki tanggung jawab besar dalam menjaga dan melindungi koleksi tersebut dari kerusakan maupun kehilangan. Tujuan utama dari penelitian ini adalah untuk mengidentifikasi strategi pelestarian yang diterapkan oleh pihak museum serta mengungkap berbagai hambatan yang dihadapi dalam proses tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data diperoleh melalui observasi langsung, wawancara dengan staf museum, serta studi dokumentasi terhadap aktivitas pelestarian. Wawancara dilakukan terhadap satu orang informan, yaitu Herina Eliasta Ginting yang menjabat sebagai Staf Koleksi Buku. Informan ini dipilih karena memiliki peran langsung serta pengetahuan yang mendalam terkait proses konservasi buku langka yang dilakukan di museum. Analisis data dilakukan menggunakan model interaktif Huberman dan Miles. Hasil penelitian menunjukkan bahwa museum telah menerapkan sejumlah strategi pelestarian, seperti pengaturan suhu dan kelembaban ruang penyimpanan, pengamanan fisik, serta tindakan preventif terhadap potensi kerusakan. Namun, pelaksanaan strategi ini masih menghadapi tantangan besar, terutama keterbatasan tenaga ahli konservasi dan anggaran operasional. Oleh karena itu, dibutuhkan peningkatan kapasitas sumber daya serta penerapan teknologi digitalisasi guna mendukung pelestarian koleksi secara lebih efektif dan berkelanjutan